Technophobia: Gender differences in the adoption of high-technology consumer products - T. G. Kotzé; O. Anderson; K. Summerfield (South African Journal of Business Management, 2016)
The advent of technology has improved consumers' daily lives; but it has also affected some consumers, by engendering fear of complex technological products. Feelings of anxiety and fear lead to the avoidance of technology; and this fear is known as `technophobia'. This study aims to establish whether gender differences in technophobia and the adoption of high-technology consumer products continue to exist in this digital age, or whether things have changed over time. The findings show that women are less optimistic than men; they exhibit higher levels of risk-aversion; and they have higher cognitive-processing than do men – when considering the purchases of high-technology products. The greatest challenge in stimulating the adoption of high-technology products is the perceived risk that a consumer experiences when making a purchasing decision. Although marketers tend to assume that in the modern digital age, men and women are consuming electronics in the same manner, this study shows that this is not necessarily the case; and as a new product is introduced to the market, marketers need to employ differentiating strategies, in order to target both men and women successfully.
Keywords: 650